Pengembangan Media Video Berbasis Powtoon pada Mata Pelajaran IPA di Kelas V - Yani Wulandari; Yayat Ruhiat; Lukman Nulhakim (Universitas Syiah Kuala, 2020)
The media cannot be separated from the learning process. The use of learning media that is not interesting and varied makes students bored. This research was conducted to produce learning media products in the form of based video animation of powtoon. To achieve these objectives used to Research and Development (RD) method. The development of instructional media focuses on Natural Sciences (IPA) subjects for the fifth-grade of primary schools. To find out the coherence between media and material, validity test have been conducted by media experts and material experts. The results of product validity by the two experts have obtained a very decent category. From the media, expert obtained a value of 89.8% and material experts 88.7%. Next, to find out the effectiveness of the media on the subject matter, a trial was conducted at SDIT. The results of a limited trial to learners obtained a very decent category with 96.36% and an evaluation by the educator of 91.1%. The results of the analysis by both experts and have been tested on students and educators, that the powtoon-based learning video media has met the criteria to be applied as a learning media for IPA